Medicinal Plant Raw Materials for Indian Drug and Pharmaceutical Industry II. Problems and Prospects of Development of Resources - Sarin, Y. K. (Indian Forester, 2003)
Proper utilization of medicinal plant resources of India requires a comprehensive approach. There are many issues concerning this area of activity. These include inventorisation , quantitative and techno-economic evaluation , standardization in terms of therapeutic efficacy and augmentation of resources through conservation , domestication and large scale cultivation. The country has been engaged in research and development in this area since long and a lot of information on different aspects is available. There is a need for retrieval and documentation of this information at national level , developing appropriate technologies and creating conditions for gainful utilization of available and developed resources. Such an exercise may go a long way for proper utilization of the resources and taking up further work to fill in the gaps.